2020
DOI: 10.7150/jca.46556
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol induced apoptosis and autophagy via the ROS/JNK signaling pathway in Human Ovarian Cancer

Abstract: Propranolol has a significant anti-cancer effect towards various cancers. Our study aimed at investigating the underlying mechanism of Propranolol's therapeutic effect towards ovarian cancer. Specifically, Propranolol significantly reduced the viability of human ovarian cancer cell lines SKOV-3 and A2780 in a dose-and time-dependent manner. Flow cytometry analysis revealed that Propranolol induced the cell cycle arrest at G2/M phase therefore leading to apoptosis. Moreover, autophagy inhibitor 3-MA markedly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 40 publications
4
20
0
Order By: Relevance
“…Similarly, propranolol also induces G0/G1/S phase arrest and apoptosis, leading to inhibition of proliferation in melanoma in vitro and in vivo by suppressing the AKT/MAPK signaling pathway [ 143 ]. Similar results were found in human ovarian cancer [ 144 ]. β2-AR blockage induces G1/S phase arrest and apoptosis in pancreatic cancer cells via Ras/Akt/NFκB pathway [ 145 ], or EFGR-Akt/ERK1/2 signaling pathway in colorectal cancer [ 146 ].…”
Section: Modulation Of the Tumor Microenvironment By Chronic Stressupporting
confidence: 88%
“…Similarly, propranolol also induces G0/G1/S phase arrest and apoptosis, leading to inhibition of proliferation in melanoma in vitro and in vivo by suppressing the AKT/MAPK signaling pathway [ 143 ]. Similar results were found in human ovarian cancer [ 144 ]. β2-AR blockage induces G1/S phase arrest and apoptosis in pancreatic cancer cells via Ras/Akt/NFκB pathway [ 145 ], or EFGR-Akt/ERK1/2 signaling pathway in colorectal cancer [ 146 ].…”
Section: Modulation Of the Tumor Microenvironment By Chronic Stressupporting
confidence: 88%
“…In agreement, previous studies reported that propranolol significantly downregulates B cell lymphoma-2 and BCl-2 associated X protein, which may be related to the TLR4/NF-κB (p65) signal in isoproterenol-induced myocardial fibrosis in mice [ 179 , 180 , 181 ]. Recently, studies demonstrated that propranolol revealed significant suppression of p38 protein expression that primarily regulates cell proliferation, migration, cell differentiation, and BCL-2 family, inhibiting apoptosis [ 182 , 183 ]. In addition, BCl-2 is considered a tissue homeostasis indicator in vascular, heart, and neurodegenerative diseases [ 184 , 185 ].…”
Section: Resultsmentioning
confidence: 99%
“…MAPK/JNK is capable of regulating apoptosis after exposure to different stresses [ 313 ], and it can also regulate autophagy [ 314 , 315 ]. In prostate cancer cells, MAPK/JNK signaling induces autophagy as a protective mechanism against celecoxib-mediated apoptosis [ 316 ].…”
Section: Autophagy and Prostate Cancermentioning
confidence: 99%